UV-activated permanganate process for micro-organic pollutant degradation: efficiency, mechanism and influencing factors - Miaomiao Ye (IWA Publishing, 2021)
Ultraviolet-activated permanganate (UV/PM) process is a novel advanced oxidation process (AOP), but its application potential remains to be evaluated. This work investigates the degradation of refractory organic pollutant by UV/PM in terms of efficiency, mechanism, and influencing factors. The target compound benzoic acid (BA), which is a micro-organic pollutant and is resistant to PM and UV treatment, can be efficiently degraded by UV/PM. The electron paramagnetic resonance spectra directly supported the formation of hydroxyl radical (HO•) and superoxide radical from UV photolysis of PM. Competitive kinetics experiments verified that acted as precursor of HO• and the good degradation performance of BA was due to the involvement of HO• and manganese(V). The rate constants of BA degradation showed a positive linear relationship with PM dosage in the range of 0.5–20 mg·L−1, and the degradation process was significantly influenced by solution pH and natural organic matters but insensitive to chloride and bicarbonate at environmentally relevant concentrations. Compared to the typical UV-based AOP UV/hydrogen peroxide, UV/PM is a little inferior, indicating that optimization and enhancement is needed for this process before its possible practical application. HIGHLIGHTS The mechanism of HO• generation from photolysis of PM was parsed.; The effects of operating parameters (e.g. PM dosage, pH, natural organic matters, alkalinity, and chloride) on UV/PM process were investigated.; UV/PM process was compared with UV/H2O2.; Optimization and enhancement is needed for UV/PM process before its possible practical application.;